As relações entre satisfação, longevidade no trabalho e comprometimento organizacional em uma empresa do segmento metalúrgico de Fortaleza - Rios, Ana Lúcia Ferreira (2009)
The objective of this paper is to study the relationship between seniority and organizational commitment as indicators of satisfaction in a family company in Fortaleza. Its relevance comes from the necessity of undertaking new themes that bring together possibilities of articulation to the theme of organizational commitment from the multidimensional pattern proposed by Rego (2003), namely: affective commitment, common future, alternatives shortage, substantial sacrifices, norm commitment, and psychological absence. The survey was conducted in a large company in the metallurgical segment in July and August 2008. Two hundred and seventy two employees from operational, administrative, coordinative, managerial and directorial levels participated in this study. Concerning the approach of the problem, the outline of this study has its base on quantitative and qualitative grounds, and its method is based on case study. The analyzed data was collected from a questionnaire. The theory used employs concepts as “organizational commitment”, “seniority”, “satisfaction”, and “management of family business” as a way to undertake patterns of relationships and influence among them. We highlight as main results the high level of affective commitment, normative commitment and communal future, as well as the low level of substantial sacrifice commitment, alternatives shortage and psychological absence perceived among all the employers of the company; we’ve concluded that employees with seniority display a slight increase in affective commitment and significant increase in normative commitment; and, finally, we have verified that employees who are not part of the family demonstrate higher levels of commitment in all dimensions of commitment as proposed by Rego (2003).